ORGANIZATION OF PRACTICAL TRAINING OF FUTURE PRIMARY SCHOOL TEACHERS IN THE CONTEXT OF CULTURAL COMPETENCE FORMATION - Nataliia Grechanyk ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
The author examines the types and duration of pedagogical practices in the UK, characterizes the main objectives of pedagogical practice in the United States in the context of the national objective to train an "effective multicultural teacher". Based on the analysis of educational and professional programs of higher education institutions of Ukraine, the author characterizes such types of pedagogical practice of future primary school teachers as: the extra-curricular and out-of-school educational practice, the pedagogical practice in children's recreation camps, the educational and nurturing practice in the first grade, the teaching and educational practice.